AB0358 WRIST BONE MINERAL DENSITY AND WRIST SYNOVITIS IN RHEUMATOID ARTHRITIS. (June 2019) - Abdelghani, Kaouther Ben; yasmine, Makhlouf; Miladi, Saoussen; Fazaa, Alia; Souebni, Leila; Chekili, Selma; Ouenniche, Kmar; Kassab, Salma; Kechaou, Sonia; Leith, Zakraoui; Laatar, Ahmed
Abstract : Background: Bone involvement in rheumatoid arthritis is characterized by focal articular bone loss around inflamed small joints of the hands.[1] Therefore, precise quantification of hand bone loss may predict the severity and the progression of the disease. Objectives: The aim of this study is to find a correlation between wrist bone mineral density (BMD) and sonographic wrist synovitis in patients with rheumatoid arthritis (RA). Methods: RA patients were examined by bone mineral density (BMD) measurement of the wrist using dual-energy X-ray absorptiometry (DXA) according to standard protocols for positionning and analysis (area measured at a level of 33%). Patients were diagnosed as having osteoporosis when the minimum T-score measured was less than -2.5 SD, osteopenia if T-score between -2, 5 and –1 SD [2]. Ultrasound of the wrist was done by an operator with experience in musculoskeletal ultrasound with an esaote My lab60 machine. The wrist joint (inferior radio-ulnar joint, medio-carpal joint and ulnar recessus) was assessed on dorsal side in Gray and Power Doppler (PDUS) scales. Semi-quantitative score was used to sum the synovitis score.[3] Statistical analysis comparing synovitis and BMD was performed using Kruskal Wallis Test, a non-parametric test (Mann–Whitney U-test) and chi-square, as appropriate. Results: The study included 24 RA patients with female predominance (sex ratio=0, 3). The mean age was 59.3 [47-71] years-old. The duration of the disease was 10.2 years [0, 83 -23] and the body mass index was 27.3 (18.97-36.98) kg/m2. RA was erosive in 75% of cases. Sixty-seven percent of patients received calcium supplementation. All women experienced already menopause. Most of them (75%) were on corticosteroids at the average dose of 5 mg [5-15], two of whom were not supplemented. Only one quarter of patients had physical activity. BMD showed that 45% of patients suffered from osteoporosis and 25% are osteopenic with a mean T-score of -1.92 [-4.3; 1.4] and mean bone mass of 0.475 g/cm 2 [0.239, 0.712]. Forty-eight wrists were assessed by ultrasound. Medio-carpal joint was the most affected in Gray scale and Doppler. Fifty-eight percent of patients had moderate to severe synovitis when combined scoring was used. Twenty nine percent of patients (29, 1%) had grade 3 at Gray Scale and 25% had Doppler scale grade 3. The wrist BMD (T-score) in RA with high disease activity was lower than those with moderate or low disease activity (-2.21 vs -2.05 and -2, 21 vs 0.6 respectively; p=0, 431). There was no correlation between BMD of the wrist and the disease duration as well as the activity of the disease DAS28 VS (respectively p = 0.4, p = 0.58).The percentages of wrist synovitis in osteoporosis group were significantly higher than in osteopenia group (81.8% vs. 66%, p=0, 03).Moroever, Gray scale grade 3 synovitis in osteoportic patients was higher than osteopenic patients (62, 5% vs 25% respectively, p=0, 041). Results also showed a correlation between BMD and doppler mode grade 3 (83%vs 16, 7 respectively, p=0, 014). Conclusion: This study shows a highly significant correlation between the BMD of the wrist and synovitis. Local inflammation of the wrist is an important factor of local bone loss that should be acted upon in order to avoid fractures, especially Colles' fracture. References: [1] Hansen M, et al. Bone loss in rheumatoid arthritis.. Scand J Rheumatol. 1996;25:367–376 [2] World Health Organization (2004) WHO scientific group on the assessment of osteoporosis at primary health care level.p. 5–7. [3] D'Agostino M L, et al.Scoring ultrasound synovitis in rheumatoid arthritis : a EULAR-OMERACT ultrasound taskforce—Part 1: definition and development of a standardised, consensus-based scoring system.RMD Open; 2017;000428. Disclosure of Interests: None declared